DEVELOPMENT OF HEALTHY LIFESTYLE SKILLS AMONG ALL CATEGORIES OF THE POPULATION: PROBLEMS AND WAYS TO OVERCOME THEM - Liliya Sagdullaevna Khalikova (Proximus Journal Publishing, 2025)
The development of healthy lifestyle skills (HLS) is an urgent task of modern society, aimed at improving public health and reducing morbidity. However, the process of developing these skills faces a number of problems affecting various social groups. This article examines the key problems that impede the development of a healthy lifestyle and proposes effective ways to overcome them
Keywords: Healthy lifestyle; skills; socio-economic factors; education